Efektivitas Budaya Refleksi Untuk Meningkatkan Kompetensi Profesional Guru Selama Masa Pandemi Covid-19 - Harsono Harsono; Sufia Munawaroh (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Teaching is a profession that requires a teacher to have special skills, a teacher cannot be done by just anyone because a teacher must be able to master four components, namely pedagogical competence, personality competence, social competence, and professional competence. Where the four components are interrelated, if a teacher is unable to master one of these competencies then he cannot be said to be a professional teacher. In this study, the researcher intends to analyze whether during the Covid - 19 pandemic teachers have fulfilled the professional competence of teachers through a culture of reflection carried out by teachers themselves. A professional teacher must be able to have the ability to teach, guide, and set a good example to his students, besides that teachers must also be able to master learning media, master the curriculum and have broad insights.